Evaluating the impacts of microplastics on agricultural soil physical, chemical properties, and toxic metal availability: An emerging concern for sustainable agriculture - Tapos Kumar Chakraborty; Md. Simoon Nice; Md. Sozibur Rahman; Baytune Nahar Netema; Khandakar Rashedul Islam; Samina Zaman; Gopal Chandra Ghosh; Md. Ripon Hossain; Asadullah Munna; Mst. Shamima Akter; Md. Abu Rayhan; Sk Mahmudul Hasan Asif; et al. (PLoS ONE, 2025)
Microplastics (MPs) are an emerging environmental issue that might endanger the health of agricultural soil. Even though several research on the particular toxicity of MPs to species have been carried out, there is little information on MPs’ impacts on soil physicochemical properties and heavy metals (HMs) availability of HMs contaminated and without contaminated soils. This study examined the changes in soil characteristics for both HMs contaminated and without contaminated soils by five distinct MPs, including Polyethylene (PE), Polyethylene terephthalate (PET), Polystyrene Foam (PS), Polyamide (PA), and a combination of these four types of MPs (Mixed MPs), at two different concentrations (0.2% and 1%; w/w), where soil incubation experiments were setup for this studies and the standard analytical techniques employed to measure soil characteristics and toxic metal availability. After the ending of soil incubation studies (90 days), significant changes have been observed for physicochemical properties [bulk density, porosity, water holding capacity, pH, electrical conductivity (EC), organic carbon (OC), and organic matter (OM)]. The soil nutrients change in descending order was found as NH4+ -N> PO43+ > Na > Ca > NO3- > Mg for lower concentrations of MPs compared to higher concentrations. The HMs availability is reducing with increasing MPs concentration and the descending order for metal availability was as follows Pb > Zn > Cd > Cr > Cu > Ni. Based on MP type, the following descending order of MPs PS > Mix (MPs) > PA > PET > PE, respectively act as a soil properties influencer. Usually, effects were reliant on MPs’ category and concentrations. Finally, this study concludes that MPs may modify metal movements, and soil quality; consequently, a possible threat will be created for soil health.